Structure of children’s skin and rules for its care – what’s new? Children’s skin structure - Garncarczyk, Agnieszka A.; Adamczyk, Katarzyna; Lubczyńska, Agnieszka; Wcisło-Dziadecka, Dominika; Antończak, Paweł; Jakubowska, Michalina (Pediatria Polska - Polish Journal of Paediatrics, 2021)
A newborns’ skin is significantly different in its structure and functions compared to that of adult skin. The differences include the structure of the epidermis, dermis, and subcutaneous tissue, as well as skin appendages. Significant disproportions are also observed in the structure of elements of the nervous, circulatory, and lymphatic systems. Rules of infant and baby care should be adapted to the requirements of their delicate, thin, and underdeveloped skin. Inadequate choice of newborn care may disturb the balance of microbiota, impairing interactions between microorganisms and between microbiota and skin. It may also impair the pH of the skin, leading to infections. Data from research present various strategies used to select dermocosmetics and care methods in the everyday hygiene of infants and babies. They now recommend that the quantity of cleaning agents should be reduced, as well as the frequency of hygienic and care treatment.